Comprehensive characterization of the in vitro and in vivo metabolites of geniposide in rats using ultra-high-performance liquid chromatography coupled with linear ion trap–Orbitrap mass spectrometer. (2nd April 2016) - Li, Yun; Cai, Wei; Cai, Qian; Che, Yanyun; Zhao, Baosheng; Zhang, Jiayu
Abstract: 1. Geniposide (genipin 1- O- glucose), one of the major bioactive constituents isolated from Fructus Gardeniae, possesses many biological activities. In this study, an efficient strategy was developed using ultra-high-performance liquid chromatography coupled with linear ion trap–Orbitrap mass spectrometer (UPLC–LTQ–Orbitrap) to profile the in vitro and in vivo metabolic patterns of geniposide in rat liver microsomes (RLMs), plasma, urine, and various tissues. And post-acquisition data-mining methods including extracted ion chromatogram (EIC), multiple mass defect filters (MMDF), fragment ion searching (FISh), and isotope pattern filtering (IPF) were adopted to characterize the known and unknown metabolites. 2. A total of 33 metabolites were detected and interpreted according to accurate mass measurement, diagnostic fragment ions, relevant drug biotransformation knowledge, and bibliography data. Among them, 17 metabolites were detected in the plasma, 31 metabolites were identified in the urine, six metabolites could be found in rat heart, 12 in liver, three in spleen, six in lung, 12 in kidney, six in brain, and four in RLMs. 3. A series of corresponding reactions such as hydrolysis, hydroxylation, taurine conjugation, hydrogenation, decarboxylation, demethylation, sulfate conjugation, cysteine S-conjugation, glucosylation, and their composite reactions were all discovered. 4. The results could provide comprehensive insights and guidance for elucidation of side effect mechanism and safety monitoring as well as for rational formulation design in drug delivery system. The newly discovered geniposide metabolites could be targets for future metabolism studies on the important chemical constituents from herbal medicines.